Building a Digital Library: The Perseus Project as a Case Study in the Humanities - Crane, Gregory (Tufts Archival Research Center, 2005)
This paper outlines some of our preliminary findings in the Perseus Project, an on-going digital library on ancient Greek culture that has been under development since 1987.